Psychotherapy in Psychosis: Experiences of Fully Recovered Service Users - Bjornestad, Jone; Veseth, Marius; Davidson, Larry; Joa, Inge; Johannessen, Jan Olav; Larsen, Tor Ketil; Melle, Ingrid; Hegelstad, Wenche ten Velden (Frontiers in Psychology, 2018)
Background Despite the evidence of the importance of including service users’ views on psychotherapy after psychosis, there is a paucity of research investigating impact on full recovery. Objectives To explore what fully recovered service users found to be the working ingredients of psychotherapy in the recovery process after psychosis. Material and Methods The study was designed as a phenomenological investigation with thematic analysis as the practical tool for analysis. 20 fully recovered service users were interviewed. Results Themes: (1) Help with the basics, (2) Having a companion when moving through chaotic turf, (3) Creating a common language, (4) Putting psychosis in brackets and cultivate all that is healthy, (5) Building a bridge from the psychotic state to the outside world. Conclusions Exposure to enduring and sensitive therapeutic pressure aimed at specific functional outcomes seemed crucial for achieving functional recovery and for counteracting social isolation. Findings indicate that psychotherapy focusing on early readjustment to everyday activities, to what is perceived as meaningful and recovery-oriented, seems to be what is preferred and called for by service users.